Features of the ancestral bilaterian inferred from Platynereis dumerilii ParaHox genes - Hui, Jerome H. L.; Raible, Florian; Arendt, Detlev (BMC biology, 2009)
The ParaHox gene cluster is the evolutionary sister to the Hox cluster. Whilst the role of the Hox cluster in patterning the anterior-posterior axis of bilaterian animals is well established, and the organisation of vertebrate Hox clusters is intimately linked to gene regulation, much less is known about the more recently discovered ParaHox cluster. ParaHox gene clustering, and its relationship to expression, has only been described in deuterostomes. Conventional protostome models (Drosophila melanogaster and Caenorhabditis elegans) are secondarily derived with respect to ParaHox genes, suffering gene loss and cluster break-up.
Gesehen am 17.05.2017